A novel measurement instrument for pressure‐injury risk assessment competence: Theoretical procedures, simulation, and psychometric quality. Issue 3 (7th February 2020) - Moura, Elaine C. Carvalho; Peres, Aida M.; Caliri, Maria H. L.; Lopez, Violeta; F. Soares, Samuel
Abstract: This study developed a measuring instrument of pressure‐injury risk assessment competence for nursing education adopting theoretical procedures based on competence structuration to support the psychometric quality. The objective of this study is testing the psychometric properties of the instrument using simulation strategy and to determine the instrument's standardisation and normalisation. A methodological study was designed. The instrument was developed by a content‐validated theoretical construct administered to 155 undergraduate nursing students from universities in the northeast and south of Brazil using simulation. The instrument was applied over three phases: before the lecture on pressure‐injury risk assessment competence, after scenario of simulation experience, and after debriefing experience. The instrument comprised 32 items. The factorial analysis found that three domains explained 64.6% and 62.18% of the total variance in post‐scenario and debriefing cases. The perfect and very high discrimination index of the instrument indicated minimal differences in measured latent trait levels. It also found that reliability was excellent (0.973 and 0.967). Moreover, an equation applicable to instruments using study's theoretical procedure was proposed. The instrument was found to be a valid, accurate, and reliable educational tool for pressure‐injury risk assessment competence.